Impact of Long-term Ozone and Fine Particle Component Exposures on Cause-Specific Mortality in the U.S. - kazemiparkouhi, fatemeh. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Civil Engineering.; Advisor: Helen Suh.; Committee: John Durant, Elena Naumova, and Justin Manjourides.; Keyword: Environmental health.